PEMBERDAYAAN PEREKONOMIAN MASYARAKAT OLEH PEMERINTAH DESA PETAI BARU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI TAHUN 2018 (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A country can be said to be prosperous when its economic development runs smoothly. Not only in urban areas, economic development should also be carried out in rural areas. National development can be said to be smooth if it is able to cover the lowest level, namely in rural areas. Rural development is an overall improvement to the social and economic conditions of life in rural areas. As with the Implementation of Village Government Empowerment in the economic development of village communities in Petai Baru Village, Singingi District, Kuantan Singingi Regency. The purpose of this research is to find out how the implementation of village government empowerment in village community economic development in Petai Baru village in terms of running community economic development in the village. The economic development of the people in Petai Baru Village is still far behind compared to the villages in Singingi District. Community economic development plans made by Village Government Officials have not been able to answer community aspirations and are not synergized with the Village Vision and Mission. The purpose of this study was to determine the implementation of Community Economic Empowerment by the Petai Baru Village Government. The theoretical concept that researchers use is empowerment theory. This research uses a qualitative approach with descriptive methods. In collecting data, researchers used interview, documentation and observation techniques. The results of the author's research are Community Economic Empowerment by the Petai Baru Village Government has not been going well, this is influenced by several things. The lack of coordination between the village government and the community, and the less than optimal performance of the KUD are also factors that affect the economic growth of the people in Petai Baru Village. Keywords: Strengthening of economic institutions, Allocation of human resources, Strengthening technology